The increase in c-fos expression in epileptic seizures is inhibited by magnetic field application, but not KCa1.1 channel expression - Akdağ, Mehmet Zülkif; Oğraş, Emrah; Doğanyiğit, Züleyha; Akyüz, Enes; Akdağ, Mahmut Berat; Okan, Aslı; Akpolat, Veysi; Küllü, İ?rem (Taylor and Francis Ltd., 2023)
The aim of this study was to understand the expression of big potassium (BK, K(Ca)1.1) channels in epileptic seizures under magnetic field application. Forty Wistar albino adult male rats were divided into five groups (n = 8). First group rats were control group. Pentylenetetrazole (PTZ) administrated to second group rats to induce the seizures with 35 mg/kg intraperitoneally injection every two days. Levetiracetam (LEV) i.p. at a dose of 108 mg/kg was given to third group rats as positive control group (PC) before 20 minutes PTZ administration. Pulsed magnetic field with 1.5 mT was exposed to the fourth group rats for 3 hours a day for 1 month as magnetic field (MF) group. 1.5 mT pulsed magnetic field was exposed to the fifth group rats for 3 hours a day for 1 month in addition to PTZ administration (PTZ+MF). K(Ca)1.1 not changed in hippocampus of PTZ rats while increased in frontal cortex and pons for PTZ group but not changed with magnetic field exposure. K(Ca)1.1 increased in heart of PTZ animals and turned back to mean control values with magnetic field exposure. Suppressing the expected increase of c-fos protein expression in seizures with magnetic field application but not being able to change the K(Ca)1.1 expression shows that new studies can be done by increasing the frequency of 1.5 mT magnetic field.
Keywords: PTZ-Kindled Model; Magnetic Field; BK Channels; Seizure; C-fos